Strategies for chassis dislocation management at container ports: repositioning and yard consolidation. (March 2021) - Ng, ManWo
Highlights: Proposes two strategies to manage chassis dislocation problem at container ports. First strategy is chassis repositioning. Chassis repositioning problem is analyzed for the case of partial demand information. Second strategy is chassis yard consolidation to reduce the variance in chassis demand. Abstract: Marine container chassis have emerged at the forefront of container port operations in the U.S., with chassis dislocation being a major new problem. To manage chassis dislocation, two strategies are presented in this paper. In the first strategy, a model is presented to support the chassis repositioning decision faced by chassis pool operators. We consider the case that an (accurate) probability distribution of chassis demand is unknown. For such a case, it is generally not possible to determine the exact optimal number of chassis to reposition. Lower and upper bounds on the optimal cost are derived that are explicitly shown to converge to the minimum cost. The second strategy is chassis yard consolidation, which has the potential to reduce the variance in chassis demand and, therefore, lead to more accurate demand forecasts. An effective algorithm to iteratively reduce the variance in chassis demand is provided. Numerical experiments are presented to illustrate the strategies.